A multidimensional quiet quitting scale: Development and test of a measure of quiet quitting - Pankaj C. Patel; Maria João Guedes; Daniel G. Bachrach; Younsung Cho (PLoS ONE, 2025)
Growing attention has focused on employees’ repeated workplace decision to engage in work-related tasks and responsibilities at a minimum level that will not lead to their dismissal. This pattern of employee work behavior, labeled “Quiet Quitting,” represents a potentially problematic organizational phenomenon, particularly given increasingly complex work demands that can lower organizational performance. However, the literature lacks both a conceptually anchored definition of the Quiet Quitting construct and an associated empirically validated measure. Through four studies (sample of graduate students, Prolific sample, snowball sample from participants around the world, and a field sample of employees), we develop and validate a two-dimensional Quiet Quitting scale. This scale will facilitate measurement of the construct and development of a more nuanced understanding of its nomological network, correlates, and consequences. Implications for theory and research bearing on employee Quiet Quitting and employee work contributions are offered.